2022
DOI: 10.3389/fendo.2021.736068
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of DNA Methylation and Gene Expression Identified Follicular Thyroid Cancer-Specific Diagnostic Biomarkers

Abstract: The diagnosis of follicular thyroid carcinoma (FTC) prior surgical resection remains a challenge, as routine screening methods, such as ultrasound or even FNAB, could not diagnose FTC preoperatively. Here, we performed an integrative analysis of DNA methylation and RNA array data from our own cohort (14 Follicular thyroid carcinoma vs 16 Benign thyroid lesion) to identify thyroid cancer-specific DNA methylation markers. We first identified differentially methylated and expressed genes and examined their correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Custom Perl scripts (Perl version 5.8.9) used for processing the FPKM expression data are available on request. Four sets of datasets GSE197852 ( 21 ), GSE3467 ( 22 ), GSE33630 ( 23 ), and GSE6004 ( 24 ) from the GEO database were used to analyze Treg-cell subpopulations. Marker genes for microenvironment cells were obtained from previous studies ( 25 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Custom Perl scripts (Perl version 5.8.9) used for processing the FPKM expression data are available on request. Four sets of datasets GSE197852 ( 21 ), GSE3467 ( 22 ), GSE33630 ( 23 ), and GSE6004 ( 24 ) from the GEO database were used to analyze Treg-cell subpopulations. Marker genes for microenvironment cells were obtained from previous studies ( 25 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…We identified a total of 13 studies, of which four were included (Supplementary Figure 1): GSE121377 20 , GSE77804 21 , GSE97466 22 , and GSE197860 23 . An additional study from GEO (GSE53051 24 ) was identified from references and was included in our analysis.…”
Section: Thyroid Cancer Array-based Methylation Studiesmentioning
confidence: 99%
“…Nonetheless, approximately 30% of thyroid nodules remain undiagnosed by pathology ( 6 , 9 ), which even leads to misdiagnosis ( 9 ). In addition, the diagnostic value of FNA is relatively low for FTC ( 10 ). Unnecessary FNA can also add to the burden on the health care system and cause considerable anxiety for patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%